The Samaritans: a profile - Pummer, Reinhard (Wm. B. Eerdmans Publishing Co, 2015)
Cover -- Title Page -- Copyright Page -- Contents -- Preface -- Abbreviations -- Illustrations -- Introduction -- i. The Identity of the Samaritans -- 1. The Samaritan View -- 2. The Traditional Jewish View -- 3. Modern Scholarly Views -- ii. Samaritans in the Hebrew Bible/Old Testament? -- iii. The Samaritans and the New Testament -- 1. The Gospel of Matthew -- 2. The Gospel of Luke and the Book of Acts -- 3. The Gospel of John -- 4. Samaritan Influence on New Testament Writings? -- iv. Samaritans in Jewish Writings of Antiquity -- 1. Apocryphal/Deuterocanonical Writings -- 2. The Dead Sea Scrolls -- 3. Flavius Josephus -- 4. Rabbinic Literature -- v. Archaeological Excavations -- 1. Mount Gerizim -- 2. Synagogues -- 3. Amulets and Oil Lamps -- 4. Ritual Baths - Miqvaʾot -- vi. Samaritan Sects -- 1. Samaritan Sources -- 2. Muslim and Karaite Sources -- 3. Patristic Sources -- vii. The Samaritans in History -- 1. Hellenistic and Early Roman Periods -- 2. Late Roman and Byzantine Periods -- 3. Early Muslim Period -- 4. Crusader Period -- 5. Mamluk Period -- 6. Ottoman Period -- 7. Modern Period -- viii. Geographical Distribution and Demography -- 1. Palestine -- 2. Diaspora -- 3. Demography -- ix. The Samaritan Pentateuch -- 1. The Nature of the Samaritan Pentateuch -- 2. Ancient Translations of the Samaritan Pentateuch -- 3. The Samaritan Pentateuch in Western Scholarship -- 4. The Samaritan Script -- x. Samaritan Literature -- 1. Exegesis -- 2. Halakhah -- 3. Liturgy -- 4. Chronicles -- 5. Linguistic Writings -- 6. Folktales -- 7. Interactions with European Scholars -- xi. Samaritan Rituals and Customs -- 1. The Samaritan Calendar -- 2. Passover and Maṣot -- 3. The Feast of Weeks -- 4. The First Day of the Seventh Month -- 5. The Day of Atonement -- 6. Tabernacles -- 7. The Eighth Day of Tabernacles - Shemini Aṣeret